NF-κB in neurodegenerative diseases: Recent evidence from human genetics - Kaltschmidt, Barbara; Helweg, Laureen P.; Greiner, Johannes F. W.; Kaltschmidt, Christian (Frontiers in Molecular Neuroscience, 2022)
The transcription factor NF-κB is commonly known to drive inflammation and cancer progression, but is also a crucial regulator of a broad range of cellular processes within the mammalian nervous system. In the present review, we provide an overview on the role of NF-κB in the nervous system particularly including its constitutive activity within cortical and hippocampal regions, neuroprotection as well as learning and memory. Our discussion further emphasizes the increasing role of human genetics in neurodegenerative disorders, namely germline mutations leading to defects in NF-κB-signaling. In particular, we propose that loss of function mutations upstream of NF-κB such as ADAM17, SHARPIN, HOIL or OTULIN affect NF-κB-activity in Alzheimer disease patients, in turn driving anatomical defects such as shrinkage of enthorinal cortex and the limbic system in early AD. Similarly, E3 type ubiquitin ligase PARKIN is positively involved in NF-κB signaling. PARKIN loss of function mutations are most frequently observed in Parkinson disease patients. In contrast to AD, relying on germline mutations of week alleles and a disease development over decades, somatic mutations affecting NF-κB activation are commonly observed in cells derived from glioblastoma multiforme (GBM), the most common malignant primary brain tumor. Here, our present review particularly sheds light on the mutual exclusion of either the deletion of NFKBIA or amplification of EGFR in GBM, both resulting in constitutive NF-κB-activity driving tumorigenesis. We also discuss emerging roles of long non-coding RNAs such as HOTAIR in suppressing phosphorylation of IκBα in the context of GBM. In summary, the recent progress in the genetic analysis of patients, particularly those suffering from AD, harbors the potential to open up new vistas for research and therapy based on TNFα/NF-κB pathway and neuroprotection.